HUBUNGAN PENGETAHUAN GIZI, PERSEPSI CITRA TUBUH DAN GANGGUAN MAKAN DENGAN STATUS GIZI REMAJA PUTRI SEKOLAH MENENGAH KEJURUAN DI KABUPATEN GRESIK - Khoirum Ma'sunnah; Heri Purnama Pribadi; Dian Agnesia (Universitas Muhammadiyah Gresik, 2021)
Adolescents are a group that is vulnerable to health problems and nutrition, especially in adolescent girls. The emergence of nutritional problems in adolescent girls can be caused by: by a extreem diet, physical activity, knowledge of nutrition, poor eating habits and lifestyle ( life style ) such as body image ( body image ). Besides that in the view of the young women a good body is a slim body so that many teenagers feel dissatisfied and not confident if the body is not slim then, this body image is the trigger level the emergence of eating disorders in adolescents. This study aims to identify and analyze the relationship between nutritional knowledge, perception of body image and disorders eating with nutritional status of adolescent girls in vocational high schools in Gresik Regency. This research is an Analytical Observational study with a Cluster Random design Sampling with respondents as many as 87 respondents who were selected by purposive sampling. The instrument used in this study was a nutritional knowledge questionnaire, questionnaire BSQ-34, EAT-26 questionnaire and food recall questionnaire 1 x 24 hours as additional data intake respondent energy. Data analysis using Chi-Square test and spearman test. The results shows that most of the respondents have good nutritional status (82.2%), there are (65.6%) respondents have sufficient knowledge of nutrition, there are (40.2%) respondents feel dissatisfied with their body image, there are (41.4%) respondents at risk of having eating disorders and eating disorders most of the respondents experienced a severe energy deficit with an average energy of 776 kcal. Test statistics between nutritional knowledge and nutritional status (p= 0.000), body image and nutritional status (p= 0.129) and eating disorders with nutritional status (p = 0.465). The conclusion, there is a relationship knowledge of nutrition with nutritional status of adolescent girls and there is no relationship body image, eating disorders with nutritional status of adolescent girls in Gresik Regency.